Penerapan Strategi Discovery Learning dengan Metode Diskusi untuk Meningkatkan Aktivitas Bertanya dan Hasil Belajar IPA Peserta Didik Kelas VI B SDN 19 Cakranegara Tahun Pelajaran 2019/2020 - Ani Sudarsih (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
This study aims to determine the effectiveness of the application of the Scientific Approach to Discovery Learning Strategy with the Discussion Method in an effort to increase questioning activities and science learning outcomes for Class VI-B students of SDN 19 Cakranegara. The benefit of this research is to encourage students to develop learning skills in groups (cognitive) and to socialize with friends as part of the real classroom learning process. And for teachers to improve the development of learning approaches and models by applying scientific and discovery learning strategies in group work learning (cooperative) with the discussion method This research was carried out in two cycles, each cycle of activities were; planning, implementation, observation and reflection. The final result of the action in the second cycle showed that the teacher's observation was 4.42, the result of the observation of the student's asking activity was (50%) with a fairly active category. While the impact of the increase in questioning activity is the increase in the acquisition of student learning outcomes reaching an average value (77.25), meaning that the indicators of success (> 4.0) and learning outcomes (> 70.00) have been exceeded. Because the indicators of success have been proven, the research was declared successful and was discontinued in cycle II.